In-match physical performance fluctuations in international Rugby Sevens competition - Peeters, A.; Carling, C.; Piscione, J.; Lacome, M. (Journal of Sports Science & Medicine, 2019)
It is widely recognised that the physical demands in rugby sevens are high especially in comparison to the 15-aside version. The aim of this study was to assess fluctuations in physical performance (running and contact loads) in international rugby sevens competition. Altogether, 32 matches played by an international team in the HSBC World Sevens Series were analyzed (63 match-observations). Players wore a validated GPS device (SensorEverywhere, France) sampling at 16Hz while an operator coded every contact action (tackles, collisions, mauls, scrums) using video analysis software (SportsCode, USA). Running load was assessed using total distance travelled (m), individually determined high-speed distance (covered at velocities > maximal aerobic speed, m) and very-high speed distance (covered at velocities > 85% maximal sprinting speed, m). The frequency of accelerations (actions > 2.5 m·s-2) and high-intensity actions (HIA, sum of high-velocity runs, accelerations and contact-related actions, n) were also calculated. A magnitude-based inferential approach to statistics was adopted and effect sizes quantified. Findings showed: 1) a small decrease in high-speed distance and number of accelerations performed during the second- versus the first-half of play suggesting a decline in running performance. (2) a moderately higher total distance and high-speed distance covered during the first and final 1-min period compared to the average for other 1-min periods, suggesting a specific reverse `J-shape` pacing profile 3) a most likely decrease in total distance, high-speed running, and to a lesser extent the number of accelerations declined following the peak 1-min period of the game. These findings provide pertinent information on changes in running performance over the course of international sevens and have implications for physical conditioning strategies.